The Role of the Principal in Improving the Quality of Education at the State Junior High School 4 Kuala, Nagan Raya Regency - Ansari, Ansari; Akmaluddin, Akmaluddin; Musdiani, Musdiani (Dinasti Research, 2025)
The purpose of the study was to analyze how the role of the principal in improving the quality of education at the driving school of State Junior High School 4 Kuala, Nagan Raya Regency. The research method is qualitative descriptive. Informants consisted of the principal, vice principal, deputy curriculum and driving teacher. Data collection using interviews, observation and documentation and analysis is descriptive qualitative. The results of the study indicate that the role of the principal as a manager in improving the Quality of Education at the driving school of State Junior High School 4 Kuala is to make planning, implementation, supervision of all activities, All problems in the school are resolved by all school residents, Instilling a disciplined attitude with a systemic system. The role of the principal as an administrator in improving the Quality of Education at the driving school of State Junior High School 4 Kuala is administrative equipment and checking the completeness of teaching and learning activities, student equipment, finance, infrastructure, public relations, correspondence, routine library and laboratory services, curriculum administration. The role of the principal as a supervisor in improving the Quality of Education at the driving school of State Junior High School 4 Kuala is to prepare an education supervision program, supervision of the implementation of teaching and learning, supervision of learning devices, utilizing the results of supervision.